Fish Population Recruitment: What recruitment means and why it matters - Ed Camp; Angela B Collins; Robert N.M. Ahrens; Kai Lorenzen (EDIS)
Recruitment, the process by which small fish transition to older, larger life stages, is probably the most important process that regulates populations of fish, but it is complicated to understand. This 6-page fact sheet written by Edward V. Camp, Robert N. M. Ahrens, Angela B. Collins, and Kai Lorenzen and published by the UF/IFAS Program in Fisheries and Aquatic Sciences, School of Forest Resources and Conservation explains the recruitment process in fish populations and why recruitment is so important to fisheries science and management. https://edis.ifas.ufl.edu/fa222